"Searching for gold" with sustainable human resources management and internal communication: Evaluating the mediating role of employer attractiveness for explaining turnover intention and performance - Daniel Roque Gomes; Neuza Ribeiro; Maria Jo\~ao Santos (Administrative Sciences, 2023)
Objective: The main objective of this study is to evaluate the impact of sustainable human resources management (SHRM) and internal communication (IC) on turnover intention (TI) and employee performance (PER) while assessing the mediating role of organizational attractiveness (AT) over these relationships. In this sense, this study intends to evaluate the effect of SHRM and IC on employee PER and TI, with AT acting as the mediator in a joint model of analysis. Methodology: To achieve the aforementioned purposes, a cross-sectional quantitative study was prepared using the Structural Equation Model (SEM). In total, 177 individuals participated in the study. Regarding gender, 62.4% were female. Participants came from all districts of Portugal and were aged from 21 years old to over 55 years old. Results: The main results show that both SHRM and IC are significantly correlated with AT, PER, and TI. Additionally, AT has a total mediation effect in the relationship between SHRM, PER, and TI and also between IC, PER, and TI. Practical implications: These results seem to support the need for organizations to invest in combined strategies and practices that aim to intertwine SHRM and IC towards the benefit of the worker. Both areas have been shown to have solid effects over PER and TI, as well as on the development of favorable worker perceptions that identify the organization as a good place to work. Practitioners should look at both SHRM and IC as valid ways of stimulating the quality of the worker-organization relationship. Incorporating these areas into common strategic planning and consecutive practices seems advisable regarding workers' performance and employee retention.
Keywords: 350; attractiveness; internal communication; performance; sustainable human resources management; turnover intention